Kajian Literatur: Penerapan Realistic Mathematics Education pada Materi Pembagian Bilangan Bulat di Sekolah Dasar - Pani, Pani Suswari (Jurnal Riset Pendidikan Matematika Jakarta, 2024)
The research objective of this literature review is to provide teachers with an in-depth understanding of implementing the realistic mathematics education (RME) approach in elementary schools. The method used is a literature review. The data collection technique used was searching and downloading several relevant national scientific articles from Google Scholar. The research instrument used was the article analysis sheet. Data analysis techniques are article collection (searching and downloading articles), data reduction (grouping), data display (article analysis), discussion, and conclusions. Based on this literature review, the RME theory was found to be related to the definition, characteristics, principles, and stages of RME as well as students' conceptions and the role of teachers in the RME approach, while the discussion presented examples of the application of RME in detail in the material of dividing integers in elementary schools. The conclusion is that teachers implementing the RME approach in elementary schools should pay attention to the important things from RME theory including the stages of the RME approach.